2018
DOI: 10.25159/2520-5293/3694
|View full text |Cite
|
Sign up to set email alerts
|

Theory-Practice Gap: The Experiences of Nigerian Nursing Students

Abstract: The “disconnect” between the body of knowledge acquired in classroom settings and the application of this knowledge in clinical practice is one of the main reasons for professional fear, anxiety and feelings of incompetence among freshly graduated nurses. While the phenomenon of the theory-to-practice gap has been researched quite extensively in high-income country settings much less is known about nursing students’ experiences in a developing country context. To rectify this shortcoming, the qualitative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…This finding was explained by the nurses' as the disconnect between what nurses say and what they do . This disconnect is a well‐known concern between nursing care discourse and practice, 36 and it slows the progress of EBP in the nursing field globally. For Bolivian nurses, this disconnect, besides the identified organizational barriers associated with EBP resources development and support by administrators and medical staff, nullifies nurses' involvement with EBP and affects important dimensions in their profession.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was explained by the nurses' as the disconnect between what nurses say and what they do . This disconnect is a well‐known concern between nursing care discourse and practice, 36 and it slows the progress of EBP in the nursing field globally. For Bolivian nurses, this disconnect, besides the identified organizational barriers associated with EBP resources development and support by administrators and medical staff, nullifies nurses' involvement with EBP and affects important dimensions in their profession.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was explained by the nurses' dialogues as the disconnect between what nurses say and what they do . This disconnect-which needs to be addressed-is a well-known concern between nursing care discourse and practice, 27 and it slows the progress of EBP in the nursing field globally. For Bolivian nurses, this disconnect, in addition to the identified organizational barriers associated to EBP resources development and support by both administrators and medical staff, does not only nullify nurses' involvement with EBP, but also affects important dimensions in their profession, for instance, the relational work dimension, by which nurses learn about one another, gain trust and respect, collaborate, and work as a team 28 to accomplish goals.…”
Section: Discussionmentioning
confidence: 99%
“…In the international literature, negative experience and low levels of practice readiness in the transition phase are linked to diverging role conceptions: A study on newly graduated nurses in Taiwan reports nurses experience difficulties in the differentiation of ‘idealised role conceptions’ and ‘actualised role conceptions’, causing anxiety, stress and a ‘reality shock’ (Cheng et al 2014). In addition, Odetola et al (2018) reported that the ‘disconnect’ between the theory and practice is one of the main reasons for professional fear, anxiety and feelings of incompetence among freshly graduated nurses.…”
Section: Discussionmentioning
confidence: 99%